Detection of glutathione with an "off–on" fluorescent biosensor based on N-acetyl-l-cysteine capped CdTe quantum dots1. Issue 19 (7th October 2015) - Tan, Xuanping; Yang, Jidong; Li, Qin; Yang, Qiong
<x xml:space="preserve">Abstract</x> This paper reports a quantum dot (QD)-based "off–on" fluorescent biosensor specifically for the determination of glutathione (GSH) with high sensitivity.